2017
DOI: 10.31219/osf.io/9sngr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Column Study of Nitrate Downward Movement and Selected Soil Chemical Properties’ Changes in Mine Spoiled Soil as Influenced by Liquid Organic Fertilizer

Abstract: Open pit coal mining is common practice to extract coal from lithosphere. This system, however, will bring about soil degradation. Organic fertilization is an alternative to recover fertility of the degraded soil. The objectives of the experiment were to determine nitrate downward movement and change of selected chemical properties in the soil column and to compare the growth of lamtoro (Leucaena leucocephala) as affected by local based liquid organic fertilizer. Column experiment was conducted usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
2

Relationship

7
0

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In contrast, LOF from cattle waste has an insignificant increment of K to the soil. Muktamar et al (2015) observed similar result where exchangeable K increased significantly to 20-25 cm depth by application of 100% LOF. Another study by Zaintun (2010) also confirmed an increase in K availability and base saturation of soil after application of LOF.…”
Section: Effect Of Lof On Selected Soil Chemical Propertiessupporting
confidence: 73%
See 2 more Smart Citations
“…In contrast, LOF from cattle waste has an insignificant increment of K to the soil. Muktamar et al (2015) observed similar result where exchangeable K increased significantly to 20-25 cm depth by application of 100% LOF. Another study by Zaintun (2010) also confirmed an increase in K availability and base saturation of soil after application of LOF.…”
Section: Effect Of Lof On Selected Soil Chemical Propertiessupporting
confidence: 73%
“…Even though the nitrate-N content in LOF from rabbit waste is higher than the other animal wastes, the residual nitrate-N in soil is about the same, indicating there is a loss of nitrate-N from the soil. The previous study by Muktamar et al (2015) demonstrates that nitrate -N moves downward to the lower part of soil profile after application of LOF. Loss of nitrate-N is a weakness of LOF application directly to surface soil.…”
Section: Effect Of Lof On Selected Soil Chemical Propertiesmentioning
confidence: 82%
See 1 more Smart Citation
“…Organic matter from organic fertilizer increased soil organic C, total N, available P, available K, CEC, water holding capacity, and water infiltration rate, improved soil structure due to formation of micro-aggregates as well as reduced bulk density [8][9][10][11][12][13][14]. Improvement of soil quality due to application of liquid organic fertilizer was detected up to 25 cm from soil surface as reported by [15]. Study by [16] also showed that organic fertilizer was able to substitute nitrogen from synthetic fertilizer.…”
Section: Introductionmentioning
confidence: 76%
“…Application of liquid organic fertilizer is reported to improve soil quality. Column study conducted by [20] pointed out that liquid organic fertilizer increased N-NO 3 , available P, exchangeable K, soil pH and decreased exchangeable Al up to the depth of 20-25 cm but available P which is only to the depth of 10-15 cm from the soil surface. The similar result reported by [15] that nitrate moved downward to a much lower depth (150-180 cm).…”
Section: Introductionmentioning
confidence: 99%